How progress ends : technology, innovation, and the fate of nations - Frey, Carl Benedikt (Princeton ; Oxford : Princeton University Press, 2025)
In How Progress Ends, Carl Benedikt Frey challenges the conventional belief that economic and technological progress is inevitable. For most of human history, stagnation was the norm, and even today progress and prosperity in the world’s largest, most advanced economies—the United States and China—have fallen short of expectations. To appreciate why we cannot depend on any AI-fueled great leap forward, Frey offers a remarkable and fascinating journey across the globe, spanning the past 1,000 years, to explain why some societies flourish and others fail in the wake of rapid technological change.
Autor zpochybňuje představu, že ekonomický a technologický pokrok je samozřejmý. Na základě historického vývoje posledního tisíciletí ukazuje, proč stagnace byla po většinu dějin normou a proč ani současné velmoci nedosahují očekávané prosperity. Kniha analyzuje faktory, které rozhodují o tom, zda společnosti v době rychlých technologických změn prosperují, nebo upadají.
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Keywords: 1.-21. století; technologický rozvoj; inovace; ekonomický růst; hospodářská stagnace; digitální transformace; monografie; analýzy; 1st-21st centuries; technological development; innovations; economic development; economic stagnation; digital transformation; monographs; analytic studies